Normally, polynomials in this format can be factored by finding two numbers whose product is equal to the last term multiplied by the coefficient of the first term, and whose sum is equal to the coefficient of the second term. The polynomial can then be broken down further.
In this case though, there are no numbers that meet that condition, so this polynomial can not be factored into terms that use simple integers. In order to find it's factors then, what you'll need to do is set the value of the statement to zero, and solve for x. This will give you two different values, which will define the numeric terms in this polynomial's factors:
Let:
x2 + 6x - 4 = 0
∴ x2 + 6x + 9 = 13
∴ (x + 3)2 = 13
∴ x + 3 = ± √13
∴ x = -3 ± √13
So we have two possible values of x, the negatives of which will be our "a" and "b" values if we express the original polynomial in the format (x + a)(x + b):
[x - (-3 + √13)][x - (-3 - √13)]
= (x + 3 + √13)(x + 3 - √13)
Which you can expand in order to show that it is indeed equal:
= x2 + (3 - √13)x + (3 + √13)x + (3 - √13)(3 + √13)
= x2 + 6x + 9 + 3√13 - 3√13 - 13
= x2 + 6x + -4
Another way you can deal with this is to separate the last term into more than one value, using a technique called "completing the square". This allows you to reduce the rest of the polynomial:
x2 + 6x + -4
= x2 + 6x + 9 - 13
= (x + 3)2 - 13
5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5
x^2 -5x-6 factors to: (x-6)(x+1)
x2 + 5x + not really sure what that extra plus is for... this is the most you can factor it... x(x + 5)
x2 - x + 30 does not have any factors. If on the other hand you wanted to factor out: x2 - x - 30 Then it can be done as follows: = x2 - 6x + 5x - 30 = x(x - 6) + 5(x - 6) = (x + 5)(x - 6)
The common factor of x^2 -x-6 and x^2-5x+6 is (x - 3)
(5x - 6)(5x + 6)
x(x2+5x+6)
5x squared plus 33x plus 18 = (5x + 3)(x + 6) x = -6, -3/5
(x + 3)(x + 2)
(5x-10)(x+3)
(x + 3)(x + 2)
-6 = 3 x -2 13 = 5 x 3 - 2 → 5x² + 13x - 6 = (5x - 2)(x + 3)
5x(x - 2)
(x - 3)(x + 8)
1
5(x2 + x + 1)
(x - 1)(5x + 7)